Transforming literacy changing lives through reading and writing - Waxler, Robert P., 1944-; Hall, Maureen P. (Bingley, U.K. : Emerald, 2011)
The book is interdisciplinary in focus and centers on enlarging teachers understanding of how reading and writing can change lives and how the language arts can contribute significantly to and change educational processes in the twenty-first century. Implicit in its argument is that although the emphasis on science and math is crucial to education in the digital edge, it remains vitally important to keep reading and writing, language and story, at the heart of the educational process. This is particularly true in a democratic society because shaping stories through human language can enhance the quality of our lives, and teach us something important about what it means to be human and vulnerable. In this sense, stories allow for self-reflection and an increased opportunity to enhance and understand emotional intelligence and human community.
ch. 1. The reading and writing classroom as the new neighborhood / Robert P. Waxler, Maureen P. Hall -- ch. 2. Deep reading and the space of the classroom / Robert P. Waxler, Maureen P. Hall -- ch. 3. The classroom adventure : to learn and to understand / Robert P. Waxler, Maureen P. Hall -- ch. 4. Literacy, focused attention, and contemplative practice / Robert P. Waxler, Maureen P. Hall -- ch. 5. Language and the arts / Robert P. Waxler, Maureen P. Hall -- ch. 6. The challenge of new technologies / Robert P. Waxler, Maureen P. Hall.
Includes bibliographical references (p. 199-206).
Keywords: Foreign Language Study -- English as a Second Language; ELT: teaching theory & methods; ELT resource books for teachers; English language -- Study and teaching -- Foreign speakers